Knowledge and practices of medication usage, storage and disposal among outpatients in a Malaysian teaching hospital: a qualitative study - Jamalud-din, Nor Akilah; Tengku Mohd. Kamil, Tengku Karmila; Hu Wei Ying, Mery; Elnaem, Mohamed Hassan Abdelaziz; Mohamed Ahmed, Abdul Karem; Mohamed Nazar, Nor Ilyani; Mohd Taufek, Nor Hidayah (2022)
Introduction: Improper storage and disposal of medications can cause pollution in the environment. Developing effective interventions tailored to local practices is important to reduce pharmaceutical wastage. Little is known concerning how Malaysian outpatients use, store, and dispose medicines. This study aimed to explore the experiences, challenges, and reflections perceived by outpatients addressing these issues. Materials and methods: A qualitative methodology was adopted by using a semi-structured interview guide to explore patients’ experiences related to their knowledge and practices of medication usage, storage, and disposal. A total of 15 patients and five caregivers were recruited at a teaching hospital in Kuantan, Pahang, for in-depth interview sessions. Each interview was recorded, transcribed verbatim, and translated into English. Data were sorted and coded using NVivo Release 1.5.1 software and subjected to thematic analysis. Results: The following themes were identified from the interviews, which were 1) incomplete labelling and instructions 2) scepticism about returning unused medications 3) lack of knowledge with varying practices 4) role of pharmacists to improve patient’s medication literacy 5) lack of accessibility to return unused medications, 6) needs of educational programmes /campaigns 7) required information on medicine prices. Conclusion: Management of medication usage, storage, and disposal seems to be multifactorial. Therefore, it is important to develop contextual strategies and effective interventions to improve patients’ knowledge and practices regarding medication usage, storage, and disposal. Future research is needed to develop and test the intervention of these components to reduce pharmaceutical wastage in the environment through best practices at all levels.